Safety of rituximab in the treatment of B cell malignancies: implications for rheumatoid arthritis - Hainsworth, John D (BioMed Central, 2003)
The chimeric anti-CD20 monoclonal antibody rituximab has been used extensively in the treatment of B cell malignancies, and more recently it has emerged as a potential treatment for rheumatoid arthritis (RA), via selective B lymphocyte depletion. Experience in oncology shows that rituximab is well tolerated in a variety of settings, with mild-to-moderate infusion related reactions following the first infusion being the most common adverse event. Current data suggest that the safety profile of rituximab in patients with RA is similar to that in oncology, but that the adverse events are less frequent and less severe in patients with RA.